Electrode material based on carbon-based metal oxide and capacitor

By using rare earth elements to modify Zn/Co-MOFs and benzoxazine monomers in the electrode material, the problem of low conductivity of transition metal oxide electrode materials is solved, and electrode materials with high specific capacitance and good cycle stability are achieved.

CN119764066AActive Publication Date: 2025-04-04SHENZHEN DONGJIA ELECTRONICS
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202311646947.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-11-30
Publication Date
2025-04-04
Estimated Expiration
2043-11-30

AI Technical Summary

Technical Problem

Due to electronic structure defects, transition metal oxide electrode materials have low conductivity, resulting in high resistivity increasing thin layer resistance and charge transfer resistance, affecting actual use.

Method used

Using carbon-based metal oxide-based electrode materials, Zn/Co-MOFs are modified by rare earth elements, and benzoxazine monomer and KOH activation are introduced during the carbonization process to form electrode materials with multi-stage pore structure and high specific surface area.

Benefits of technology

The electrochemical activity, conductivity and stability of the material are significantly improved, the specific capacitance value and capacitance retention rate are improved, and good cycling stability is shown.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119764066A_ABST
    Figure CN119764066A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of capacitors, in particular to an electrode material based on a carbon-based metal oxide and a capacitor, the electrode material is prepared from MOFs and a benzoxazine monomer, the weight ratio of the MOFs to the benzoxazine monomer is (1-5): (1-5), the prepared electrode material has a high specific capacitance value, meanwhile, the capacitance retention rate is high, and the performance of the capacitor is improved. Good cycling stability is shown.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of capacitors, and in particular to an electrode material and a capacitor based on carbon-based metal oxides. Background Art

[0002] Supercapacitors are generally composed of positive and negative electrodes, electrolyte solutions and diaphragms, among which the electrodes are the core part of supercapacitors and the basis for efficient conversion and storage of electrochemical energy. Therefore, the research on electrode materials is the key to the development of supercapacitors.

[0003] Transition metal oxides are another major class of supercapacitor electrode materials, with high specific capacitance, high energy density, and excellent pseudocapacitive properties. According to relevant literature, transition metal oxide electrodes can produce large specific capacitance and high energy density at low scan rates and low current densities. However, most transition metal oxides have very low material conductivity due to electronic structural defects. High resistivity increases sheet resistance and charge transfer resistance, especially at high current densities, which can cause a large loss of voltage, seriously affecting practical use. Summary of the invention

[0004] Purpose of the invention: In view of the above technical problems, the present invention proposes an electrode material and a capacitor based on carbon-based metal oxides.

[0005] The technical solutions adopted are as follows:

[0006] A carbon-based metal oxide-based electrode material is prepared from MOFs and benzoxazine monomers, wherein the weight ratio of the MOFs to the benzoxazine monomers is 1-5:1-5.

[0007] Furthermore, the MOFs are rare earth element modified Zn / Co-MOFs.

[0008] Furthermore, the preparation method of the rare earth element modified Zn / Co-MOFs is as follows:

[0009] Add water-soluble zinc salt, water-soluble cobalt salt, nitrogen-containing heterocyclic ligand and polyvalent aromatic carboxylic acid ligand into an alcohol solvent and mix well. The resulting mixed solution is subjected to solvothermal reaction at 120-140°C for more than 4 hours. The product is collected and dispersed in an alcohol solvent. Add a water-soluble rare earth salt and heat to reflux for more than 24 hours.

[0010] Furthermore, the water-soluble rare earth salt is a water-soluble terbium salt or a water-soluble europium salt.

[0011] Furthermore, the molar ratio of the water-soluble zinc salt, the water-soluble cobalt salt and the water-soluble rare earth salt is 1:2:0.1-0.5.

[0012] Furthermore, the molar ratio of the nitrogen-containing heterocyclic ligand to the polyvalent aromatic carboxylic acid ligand is 1-5:1-5.

[0013] Furthermore, the structural formula of the benzoxazine monomer is as follows:

[0014]

[0015] Here, R is any one of hydrogen, hydroxyl, carboxyl, amino, cyano, and sulfonic acid groups.

[0016] Furthermore, the benzoxazine monomer is the following compound:

[0017]

[0018]

[0019] Furthermore, the preparation method of the above-mentioned electrode material based on carbon-based metal oxide is as follows:

[0020] The benzoxazine monomer is dissolved in a mixed solvent of N,N-dimethylformamide and n-propanol, and then MOFs is added, ultrasonic oscillation is performed for more than 30 minutes, and the solvent is evaporated under reduced pressure to obtain a precursor. The precursor is heated to 200-250°C and kept for curing for 1-3 hours, and then heated to 550-600°C under nitrogen protection for 1-3 hours. The obtained product is mixed and ground with KOH, and then heated to 850-950°C in a mixed atmosphere of nitrogen and hydrogen for 1-3 hours. The product is washed with water until neutral and then dried.

[0021] The present invention also provides a capacitor, comprising the above-mentioned carbon-based metal oxide-based electrode material.

[0022] Beneficial effects of the present invention:

[0023] The present invention provides an electrode material based on carbon-based metal oxides. Rare earth elements are used to modify Zn / Co-MOFs as core bodies. Rare earth element-doped Zn / Co bimetallic oxides are obtained during carbonization. Compared with single metals, bimetallic oxides have more metal sites for redox reactions and generate larger ion transmission channels, thereby significantly improving the electrochemical activity of the material. The skeleton of organic ligands in MOFs is modified with rare earth elements by covalent post-synthesis modification. While maintaining the original topological structure, the porosity is improved. Rare earth elements have a good regulating effect on the electronic properties of bimetallic oxides. The obtained carbonized product has more valence adjustable sites, better conductivity and higher stability.

[0024] The introduction of polyvalent aromatic carboxylic acid ligands overcomes the disadvantage of unstable skeletons of nitrogen-containing heterocyclic ligands alone. The rigid groups strengthen the skeleton structure of MOFs, and carboxylic acids can combine with rare earth elements to form a stable skeleton structure, thus showing the diversity of coordination.

[0025] The polymer after thermal curing of benzoxazine monomer is coated on the surface of MOFs, and after carbonization, it presents a certain spherical morphology, with extremely high specific surface area and multi-level pore structure. These structural characteristics are conducive to the improvement of conductivity, ion / mass transfer, charge or ion aggregation at the electrode-electrolyte interface, and the generation of pseudocapacitance, so that the material has high capacitance performance;

[0026] Adding KOH for activation can generate a large amount of gas during the carbonization process. At high temperature, these gases etch the carbon material and expand the pore volume, thereby increasing the contact area between the electrolyte and the pores, enhancing the double electrical layer effect, and improving the electrochemical activity. Hydrogen has a strong reducing property. Carbonization in a mixed atmosphere of nitrogen and hydrogen can reduce some metal ions to a lower valence state, and at the same time introduce oxygen vacancies in the generated bimetallic oxide, thereby improving the conductivity.

[0027] After testing, it is found that the electrode material prepared by the present invention has a higher specific capacitance value and a higher capacitance retention rate, showing good cycle stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 This is a SEM image of the electrode material prepared in Example 1;

[0029] Figure 2 This is a locally enlarged SEM image of the electrode material prepared in Example 1. DETAILED DESCRIPTION

[0030] If the specific conditions are not specified in the examples, the experiments were carried out under conventional conditions or the conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments is not specified, they are all conventional products that can be purchased commercially. The techniques not mentioned in the present invention are all referenced to the prior art. Unless otherwise specified, the following examples and comparative examples are parallel experiments, using the same processing steps and parameters.

[0031] Embodiment 1:

[0032] A method for preparing an electrode material based on a carbon-based metal oxide:

[0033] 5.68g zinc nitrate (0.03mol), 10.97g cobalt nitrate (0.06mol), 12.32g 2-methylimidazole (0.15mol) and 24.9g terephthalic acid (0.15mol) were added to 250ml methanol and mixed. The resulting mixture was transferred to a polytetrafluoroethylene reactor, sealed and heated to 135°C for solvent thermal reaction for 8h. The product was collected, washed with methanol and dried, added to 500ml methanol, ultrasonically dispersed for 30min, and then 0.005mol terbium nitrate was added. The temperature was raised to reflux for 48h to obtain Tb-modified Zn / Co-MOFs.

[0034] 1.5 mol of paraformaldehyde, 750 mmol of furfurylamine and 100 ml of toluene were added into a three-necked flask, stirred at room temperature for 1 hour, and then 750 mmol of m-methylphenol was dissolved in 200 ml of toluene and added, stirred and refluxed for 6 hours. After the reaction was completed, it was cooled to room temperature, and the reaction solution was washed three times with deionized water. 3 L of n-hexane was added dropwise to the organic phase, and the temperature was lowered to 5°C, stirred and crystallized for 10 hours, filtered, and the product was collected and dried to obtain a benzoxazine monomer;

[0035]

[0036] 10g of benzoxazine monomer was dissolved in a mixed solvent consisting of 50ml of N,N-dimethylformamide and 50ml of n-propanol, and then 10g of Tb-modified Zn / Co-MOFs was added, ultrasonic oscillation was performed for 45min, and the solvent was evaporated under reduced pressure to obtain a precursor. The precursor was heated to 200°C and kept for curing for 2h, and then heated to 600°C for 2h under nitrogen protection. The obtained product was mixed and ground evenly with 40g of KOH, and then heated to 950°C for 2h in a mixed atmosphere of nitrogen and hydrogen with a volume ratio of 5:1. The product was washed with water until neutral and then dried.

[0037] Embodiment 2:

[0038] A method for preparing an electrode material based on a carbon-based metal oxide:

[0039] 5.68g zinc nitrate (0.03mol), 10.97g cobalt nitrate (0.06mol), 12.32g 2-methylimidazole (0.15mol) and 24.9g terephthalic acid (0.15mol) were added to 250ml methanol and mixed. The resulting mixture was transferred to a polytetrafluoroethylene reactor, sealed and heated to 135°C for solvent thermal reaction for 8h. The product was collected, washed with methanol and dried, added to 500ml methanol, ultrasonically dispersed for 30min, and then 0.005mol terbium nitrate was added. The temperature was raised to reflux for 48h to obtain Tb-modified Zn / Co-MOFs.

[0040] 1.5 mol of paraformaldehyde, 750 mmol of furfurylamine and 100 ml of toluene were added into a three-necked flask, stirred at room temperature for 1 hour, and then 750 mmol of m-methylphenol was dissolved in 200 ml of toluene and added, stirred and refluxed for 6 hours. After the reaction was completed, it was cooled to room temperature, and the reaction solution was washed three times with deionized water. 3 L of n-hexane was added dropwise to the organic phase, and the temperature was lowered to 5°C, stirred and crystallized for 10 hours, filtered, and the product was collected and dried to obtain a benzoxazine monomer;

[0041]

[0042] 10g of benzoxazine monomer was dissolved in a mixed solvent consisting of 50ml of N,N-dimethylformamide and 50ml of n-propanol, and then 10g of Tb-modified Zn / Co-MOFs was added, ultrasonic oscillation was carried out for 45min, and the solvent was evaporated under reduced pressure to obtain a precursor. The precursor was heated to 250°C and cured for 3h, and then heated to 600°C under nitrogen protection for 3h. The obtained product was mixed and ground evenly with 40g of KOH, and then heated to 950°C in a mixed atmosphere of nitrogen and hydrogen with a volume ratio of 5:1 for 3h. The product was washed with water until neutral and then dried.

[0043] Embodiment 3:

[0044] A method for preparing an electrode material based on a carbon-based metal oxide:

[0045] 5.68g zinc nitrate (0.03mol), 10.97g cobalt nitrate (0.06mol), 12.32g 2-methylimidazole (0.15mol) and 24.9g terephthalic acid (0.15mol) were added to 250ml methanol and mixed. The resulting mixture was transferred to a polytetrafluoroethylene reactor, sealed and heated to 135°C for solvent thermal reaction for 8h. The product was collected, washed with methanol and dried, added to 500ml methanol, ultrasonically dispersed for 30min, and then 0.005mol terbium nitrate was added. The temperature was raised to reflux for 48h to obtain Tb-modified Zn / Co-MOFs.

[0046] 1.5 mol of paraformaldehyde, 750 mmol of furfurylamine and 100 ml of toluene were added into a three-necked flask, stirred at room temperature for 1 hour, and then 750 mmol of m-methylphenol was dissolved in 200 ml of toluene and added, stirred and refluxed for 6 hours. After the reaction was completed, it was cooled to room temperature, and the reaction solution was washed three times with deionized water. 3 L of n-hexane was added dropwise to the organic phase, and the temperature was lowered to 5°C, stirred and crystallized for 10 hours, filtered, and the product was collected and dried to obtain a benzoxazine monomer;

[0047]

[0048] 10g of benzoxazine monomer was dissolved in a mixed solvent consisting of 50ml of N,N-dimethylformamide and 50ml of n-propanol, and then 10g of Tb-modified Zn / Co-MOFs was added, ultrasonic oscillation was carried out for 45min, and the solvent was evaporated under reduced pressure to obtain a precursor. The precursor was heated to 250°C and kept for curing for 1h, and then heated to 600°C under nitrogen protection for 1h. The obtained product was mixed and ground evenly with 40g of KOH, and then heated to 850°C in a mixed atmosphere of nitrogen and hydrogen with a volume ratio of 5:1 and kept for 3h. The product was washed with water until neutral and then dried.

[0049] Comparative Example 1:

[0050] The method is basically the same as Example 1, except that Zn / Co-MOFs is used instead of Tb to modify Zn / Co-MOFs;

[0051] The preparation method of Zn / Co-MOFs is as follows:

[0052] 5.68 g zinc nitrate (0.03 mol), 10.97 g cobalt nitrate (0.06 mol), 12.32 g 2-methylimidazole (0.15 mol) and 24.9 g terephthalic acid (0.15 mol) were added to 250 ml methanol and mixed. The resulting mixture was transferred to a polytetrafluoroethylene reactor, sealed and heated to 135°C for solvent thermal reaction for 8 hours. The product was collected, washed with methanol and dried.

[0053] Comparative Example 2:

[0054] The same as Example 1, except that polystyrene is used instead of benzoxazine monomer;

[0055] The preparation method of the electrode material is as follows:

[0056] 5.68g zinc nitrate (0.03mol), 10.97g cobalt nitrate (0.06mol), 12.32g 2-methylimidazole (0.15mol) and 24.9g terephthalic acid (0.15mol) were added to 250ml methanol and mixed. The resulting mixture was transferred to a polytetrafluoroethylene reactor, sealed and heated to 135°C for solvent thermal reaction for 8h. The product was collected, washed with methanol and dried, added to 500ml methanol, ultrasonically dispersed for 30min, and then 0.005mol terbium nitrate was added. The temperature was raised to reflux for 48h to obtain Tb-modified Zn / Co-MOFs.

[0057] Dissolve 10g of polystyrene in 100ml of toluene, then add 10g of Tb-modified Zn / Co-MOFs, and oscillate ultrasonically for 45min. Evaporate the solvent under reduced pressure to obtain a precursor. Heat the precursor to 200℃ and keep it for 2h for curing. Then heat it to 600℃ for 2h under nitrogen protection. Mix the product with 40g of KOH and grind it evenly. Then heat it to 950℃ in a mixed atmosphere of nitrogen and hydrogen with a volume ratio of 5:1 and keep it for 2h. Wash the product with water until it is neutral and then dry it.

[0058] Performance Test:

[0059] The electrochemical performance of the electrode materials prepared in Examples 1-3 and Comparative Examples 1-2 of the present invention was tested using a three-electrode system;

[0060] The working electrode is made of electrode material, acetylene black and polytetrafluoroethylene with a mass ratio of 8:1:1, which are dissolved in ethanol and then ground and mixed, and coated on a 1cm×1cm nickel foam, and then dried and compacted. A saturated calomel electrode is used as a reference electrode, a platinum sheet is used as a counter electrode, and 1mol / L H2SO4 is used as an electrolyte to form a three-electrode system. The specific capacitance of the three-electrode system at a current density of 1A / g and the capacitance retention rate after 10,000 cycles are tested using a CH1760D electrochemical workstation. The test results are shown in Table 1:

[0061] Table 1:

[0062]

[0063] As can be seen from Table 1 above, the electrode material prepared by the present invention has a higher specific capacitance value and a higher capacitance retention rate, showing good cycle stability;

[0064] By comparing the data of Example 1 with that of Comparative Example 1, it can be seen that Tb modification plays a positive role in improving the specific capacitance and cycle stability of the electrode material. It may be that Tb atoms have a good regulating effect on the electronic properties of metal oxides, and the obtained carbonization product has more valence adjustable sites, better conductivity and higher stability.

[0065] By comparing the data of Example 1 with that of Comparative Example 2, it can be seen that the carbonized product after curing of the benzoxazine monomer is more suitable as an electrode material for a capacitor than polystyrene.

[0066] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. An electrode material based on a carbon-based metal oxide, characterized in that: The invention is prepared from MOFs and benzoxazine monomers, wherein the weight ratio of the MOFs and the benzoxazine monomers is 1-5:1-5.

2. The electrode material based on carbon-based metal oxide according to claim 1, characterized in that The MOFs are rare earth element modified Zn / Co-MOFs.

3. The electrode material based on carbon-based metal oxide according to claim 2, characterized in that The preparation method of the rare earth element modified Zn / Co-MOFs is as follows: Add water-soluble zinc salt, water-soluble cobalt salt, nitrogen-containing heterocyclic ligand and polyvalent aromatic carboxylic acid ligand into an alcohol solvent and mix well. The resulting mixed solution is subjected to solvothermal reaction at 120-140°C for more than 4 hours. The product is collected and dispersed in an alcohol solvent. Add a water-soluble rare earth salt and heat to reflux for more than 24 hours.

4. The electrode material based on carbon-based metal oxide according to claim 3, characterized in that The water-soluble rare earth salt is a water-soluble terbium salt or a water-soluble europium salt.

5. The electrode material based on carbon-based metal oxide according to claim 3, characterized in that The molar ratio of the water-soluble zinc salt, the water-soluble cobalt salt and the water-soluble rare earth salt is 1:2:0.1-0.

5.

6. The electrode material based on carbon-based metal oxide according to claim 3, characterized in that The molar ratio of the nitrogen-containing heterocyclic ligand to the polyvalent aromatic carboxylic acid ligand is 1-5:1-5.

7. The electrode material based on carbon-based metal oxide according to claim 1, characterized in that The structural formula of the benzoxazine monomer is shown below: Here, R is any one of hydrogen, hydroxyl, carboxyl, amino, cyano, and sulfonic acid groups.

8. The electrode material based on carbon-based metal oxide according to claim 1, characterized in that The benzoxazine monomer is the following compound:

9. The electrode material based on carbon-based metal oxide according to claim 1, characterized in that The preparation method is as follows: The benzoxazine monomer is dissolved in a mixed solvent of N,N-dimethylformamide and n-propanol, and then MOFs is added, ultrasonic oscillation is performed for more than 30 minutes, and the solvent is evaporated under reduced pressure to obtain a precursor. The precursor is heated to 200-250°C and kept for curing for 1-3 hours, and then heated to 550-600°C under nitrogen protection for 1-3 hours. The obtained product is mixed and ground with KOH, and then heated to 850-950°C in a mixed atmosphere of nitrogen and hydrogen for 1-3 hours. The product is washed with water until neutral and then dried.

10. A capacitor, characterized in that: The invention comprises the electrode material based on carbon-based metal oxide as described in any one of claims 1 to 9.

Citation Information

Patent Citations

  • Preparation method of nitrogen-oxygen co-doped porous carbon materials based on bio-based benzoxazine

    CN108640113A

  • Preparation method and application of metal oxide nanoparticle loaded three-dimensional graphene material

    CN113060721A

  • Carbon-based electrode material with ultrahigh specific capacitance and preparation method thereof

    CN115240989A

  • Carbon material as well as preparation method and application thereof

    CN115554982A

  • Preparation method and application of supercapacitor electrode material Ln (s)-Co compound

    CN115785464A